The role of mental health and self-efficacy in the pain experience of patients with amyotrophic lateral sclerosis. Issue 3 (18th May 2016) - Stephens, Helen E.; Lehman, Erik; Raheja, Divisha; Yang, Chengwu; Walsh, Susan; Simmons, Zachary
Abstract: Complex interactions between pain, depression, and anxiety impact quality of life in patients with ALS. Psychological approaches to pain control may be useful. This study explored the role of self-efficacy in mitigating pain. Individuals registered with the Agency for Toxic Substances and Disease Registry National ALS Registry and who experienced pain were invited to participate in an online survey. Subjects completed the Brief Pain Inventory-Short Form, Hospital Anxiety and Depression Scale, and Chronic Pain Self-Efficacy Scale. Correlations between variables were determined. Multiple linear regression models assessed relationships between depression, anxiety and self-efficacy predictions, and pain severity, interference, and relief. Results recorded that there were 197 participants (58% males, mean age 59 ± 10 years). Cases or borderline cases of depression or anxiety were common. Mean levels of pain were moderate. Higher pain self-efficacy scores predicted lower pain severity, lower pain interference, and higher pain relief with treatment. As depression scores increased, pain interference with daily life was higher. In conclusion, anxiety and depression are common in patients with ALS and pain. Self-efficacy appears to mitigate pain. A multifactorial approach to pain management should be considered in these patients, addressing mental health and self-efficacy to augment pharmacologic pain treatments.